A tool for investigating the differential functions of aggressive behavior in the face‐to‐face and cyber context: Extending the Cyber‐Aggression Typology Questionnaire. Issue 5 (7th May 2020) - Graf, Daniel; Yanagida, Takuya; Maschler, Albert; Spiel, Christiane
Abstract: Aggressive behavior in the face‐to‐face and cyber contexts is driven by underlying aggression (i.e., functions of aggressive behavior). Common theories of aggression distinguish between reactive (e.g., rage) and proactive (e.g., seeking to achieve power and affiliation) aggression. However, according to the quadripartite violence typology, this distinction conflates aspects of motivational valence with self‐regulatory processes. The Cyber‐Aggression Typology Questionnaire (CATQ; Runions et al., 2017, Aggress Behav, 43(1), pp. 74–84) overcomes this weakness by identifying four types of cyber‐aggression (impulsive‐aversive/rage, controlled‐aversive/revenge, controlled‐appetitive/reward, and impulsive‐appetitive/recreation cyber‐aggression). However, the CATQ only considers aggression in cyberspace. We extended the CATQ to the face‐to‐face context by developing a corresponding Face‐to‐Face Aggression Typology Questionnaire (FATQ). The aim of this study was to investigate factorial and convergent validity and metric measurement invariance between four‐factorial cyber and face‐to‐face aggression. In total, 587 students from six Austrian universities filled out the CATQ, the FATQ, and additional scales during regular university lectures to examine convergent validity. Confirmatory factor analysis supported the four‐factor structure of both questionnaires, after excluding inconclusive items from the impulsive‐aversive/rage subscale of the FATQ. These items were also removed from the CATQ to obtain two symmetric questionnaires. Metric measurement invariance between the CATQ and the FATQ was confirmed. Convergent validity was largely observed. Our results support an extended four‐factor model of aggression. Having two parallel questionnaires, the FATQ and CATQ, enables future studies to investigate commonalities and differences in underlying drivers of aggressive behavior in the cyber and face‐to‐face contexts.